Radiopharmaceuticals : introduction to drug evaluation and dose estimation - Williams, Lawrence E. (Boca Raton : CRC Press, 2011)
'This comprehensive overview details the process of radiopharmaceutical development, from cellular studies to animal experiments to the design and implementation of clinical trials. It examines the relative benefits of various radiopharmaceuticals and provides guidance on dose estimation and agent selection. Utilizing figures of merit for quantitative assessment, it covers standard medical internal radiation dose (MIRD), absorbed dose method for imaging agents, vivo methods for obtaining activity data, errors of activity estimation techniques, phantom-based and patient-based dose estimates and their associated uncertainties, and options available to clinical physicists. Supported by numerous examples from clinical trials, it discusses two and three dimensional estimation processes, including modern hybrid scanners such as SPECT /CT and PET/CT'--Provided by publisher.
Keywords: Radiopharmaceuticals; Clinical Trials as Topic; Radiopharmaceuticals -- administration & dosage